2004
DOI: 10.1007/s00277-004-0908-1
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dexamethasone as a first- and second-line treatment of idiopathic thrombocytopenic purpura in adults

Abstract: The current first-line choice of treatment of idiopathic thrombocytopenic purpura (ITP) in adults, prednisone, is effective but has many side effects. Furthermore, reduction of the dose leads to a relapse of ITP in a majority of cases. Courses of high-dose dexamethasone (HD) aim to avoid these problems. We treated 36 patients with newly diagnosed or recurrent ITP with an 8-day course of HD, with a peak dose of 40 mg/day. The courses were repeated up to a maximum of six courses, with a 28-day interval. Acute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…We have obtained a persistent response rate of 66.7% (32/48 evaluable adult patients) without any therapy, whereas in the Cheng et al study a persistent response rate of 42% was reported. 21 Furthermore, our data seem to be similar to those of Borst et al, 23 who more recently reported a long-term response of 59%. However, they observed an adverse event rate of 22%, and in our 2 studies adverse event rates were 13.5% and 2.1%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…We have obtained a persistent response rate of 66.7% (32/48 evaluable adult patients) without any therapy, whereas in the Cheng et al study a persistent response rate of 42% was reported. 21 Furthermore, our data seem to be similar to those of Borst et al, 23 who more recently reported a long-term response of 59%. However, they observed an adverse event rate of 22%, and in our 2 studies adverse event rates were 13.5% and 2.1%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Even with the difference of the criteria of response and the number of cycles of HD-Dexa, an initial response was obtained in more than 70% in the untreated groups. In the present analysis HD-Dexa regimens yielded a similar good response in comparison with historical data (3)(4)(5)8). Meanwhile, as to time to next treatment, the duration time was short for the untreated ITP patients.…”
Section: Discussionsupporting
confidence: 66%
“…8 One study showed that a single 4-day cycle of dexamethasone at 40 mg/day was often effective in treating ITP patients at diagnosis; 8 however, treatment with dexamethasone is less effective in patients with persistent and especially chronic ITP. [9][10][11] Another study demonstrated that three or more 4-day cycles of dexamethasone were more efficacious than one cycle. 12 Rituximab is a monoclonal antibody that binds to the CD20 antigen present on B lymphocytes.…”
Section: Introductionmentioning
confidence: 99%